Understanding the relationship between trade adjustment and forest density in lower, lower-middle, upper-middle, and high-income countries - Rizwan Akhtar; Jamal Hussain; Zhuang Miao; Lingchao Li; Tran Cuong; Baodong Cheng; Rashid Ali; Sajjad Haider; Hajira Murad Ali (Chinese Journal of Population, Resources and Environment, 2025)
Forests are essential for both ecological and economic aspects. Most rural people in developing countries rely on forest resources for their livelihood. Since 1980, trade has substantially affected forest cover, density, and management in developing countries. Few studies have examined how changes in trade structure and international trade in primary commodities affect forest density. To better understand the relationship between trade, trade structure adjustment, and forest density, this study examined 52 developing countries across four income levels: high income (HI), low income (LI), upper-middle income (UMI), and lower-middle income (LMI). We compared studies on historical changes in forest cover with those on forest density. For alternative outcomes, we used a generalized method of moments (GMM) model for the entire panel and a random-effects model for various income categories. The results show that the percentage of non-primary goods exported (PNPEXP) and total manufacturing and services exported (TEXP) significantly impact forest density. This suggests that trade and trade structure can improve a country’s forest density conditions.